Foreign Interest Rate, Monetary Policy and Bank Credit - Taufiq Carnegie Dawood (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
This paper concluded that domestic credit provided by banks in home country is affected by interest rates from abroad. And its effect on credit depends on the intensity of the foreign shock’s influence towards income in contrast to cost from interest in the balance sheet of banks of the home country. Conversely, a monetary contraction reduces the amount of credit provision by bank, with a delayed response (lag).And both monetary policy of home country and interest rate of abroad gives important effect on the provision of domestic credit.